GIS-material for the archaeological project: A Funnel Beaker settlement in Kimstad - Excavation preceding rebuilding of commuter train station in Kimstad - Swedish National Heritage Board, UV Öst (Uppsala University, 2024)
The information in the abstract is translated from the archaeological report:
The Swedish National Heritage Board's contract archaeology division, UV Öst, has performed a preliminary investigation during autumn 2005 and a subsequent final excavation during summer 2006 in Kimstad, within the property Ask 5:1, Norrköping municipality. The municipality was planning to build a new train station that would affect the prehistoric settlement site RAÄ 258. The excavations covered the remains of a neolithic house and a few other features. Two samples of charcoal have been dated to the Late Mesolithic, c. 4300 BC. A third sample was dated to the Early Neolithic, c. 3700 BC. About 3 kg of early neolithic pottery was collected. A polished axe of diabase supports this dating, which seems to bee the earliest phase of the settlement. The house was supported by one row of posts and included remains of hearths, pits and a larger storage pit.

Purpose:
The information in the purpose is translated from the archaeological report:
The aim of the preliminary investigation was to delimit the archaeological site and to try to determine its character and dating. The aim of the final excavation was to determine the function and dating of the site and thus get a more definite understanding of the period of time the site has been used as well as its function. The aim was also to place the site in a larger perspective, comparing it to other settlement sites from the same era.

The data is available in two formats: a ZIP file containing GIS shapefiles connected to an Access datafile containing information pertaining to excavation area, finds, object types along with other metadata regarding the archaeological investigation. The second ZIP file consists of corresponding .gml and .xlsx files.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
Riksantikvarieämbetet UV Öst utförde under hösten 2005 en arkeologisk förundersökning och en påföljande slutundersökning under försommaren 2006 i Kimstad, inom fastigheten Ask 5:1, Norrköpings kommun. Norrköpings kommun avser att bygga en ny pendeltågstation som skulle komma att beröra fornlämning RAÄ 258, en förhistorisk boplats. Undersökningarna omfattade lämningar efter ett neolitiskt hus samt ett fåtal övriga anläggningar. Analyserat kol har givit två senmesolitiska dateringar från cirka 4300 f Kr. En tredje datering gav en tidigneolitisk datering, cirka 3700 f Kr. Vid undersökningen tillvaratogs cirka 3 kg tidigneolitisk keramik. En slipad yxa av diabas stöder denna datering som också verkar vara boplatsens yngsta fas. Det neolitiska huset utgjordes av en så kallad mesulakonstruktion samt lämningar efter härdar, gropar och en större förrådsgrop.

Syfte:
Informationen i syfte är hämtad ur rapporten för undersökningen:
Syftet med förundersökningen var att avgränsa fornlämningsområdet och försöka avgöra karaktär och datering. Syftet inför slutundersökningen var att funktionsbestämma och datera fornlämningen och således försöka få en mer definitiv uppfattning om platsens användningstid och funktion. Likaså var förhoppningen att fornlämningen skulle kunna sättas in i ett större perspektiv med liknande boplatser från samma tid.

Data finns tillgängligt i två olika format: en ZIP-fil innehåller GIS-filer (shp) samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen. Den andra ZIP-filen består av gml- och xlsx-filer med motsvarande data
GIS-material för arkeologiskt projekt: En Vråboplats i Kimstad - Inför ombyggnad till ny pendeltågstation i Kimstad
Keywords: stone age; stenålder; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi; Fieldwork archive; Fieldwork archive